A new genus and species of felt scale (Hemiptera: Coccomorpha: Eriococcidae) from New Caledonia on an endemic species of Casuarinaceae - Hodgson, Chris; Germain, Jean-François; Matile-Ferrero, Danièle (Zootaxa, 2018)
A new genus of Eriococcidae, Dzumacoccus Hodgson gen. n., is erected for a new species, Dzumacoccus baylaci Hodgson, Germain & Matile-Ferrero, feeding on Gymnostoma poissonianum, a species of Casuarinaceae endemic to New Caledonia. The adult female and first-instar nymph are described and illustrated.